Individual and Combined Associations of Glucose Metabolic Components With Cognitive Function Modified by Obesity - He, Ruixin; Zheng, Ruizhi; Li, Jie; Cao, Qiuyu; Hou, Tianzhichao; Zhao, Zhiyun; Xu, Min; Chen, Yuhong; Lu, Jieli; Wang, Tiange; Xu, Yu; Bi, Yufang; et al. (Frontiers in Endocrinology, 2021)
Aim: We aimed to detect individual and combined effect of glucose metabolic components on cognitive function in particular domains among older adults. Methods: Data of 2925 adults aged over 60 years from 2011-2014 National Health and Nutrition Examination Survey were analyzed. Individuals’ cognitive function were evaluated using the Digit Symbol Substitution Test (DSST), the Animal Fluency Test (AF), the Consortium to Establish a Registry for Alzheimer’s Disease Immediate Recall (CERAD-IR) and CERAD Delayed Recall (CERAD-DR). Participants’ glucose metabolic health status was determined based on fasting plasma glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR), glycated hemoglobin (HbA1c) and 2-hour postload glucose. Linear regression models were used to delineate the associations of cognitive function with individual glucose metabolic component and with metformin use. Logistic regression models were performed to evaluate the associations of cognition with the number of glucose metabolic risk components. Results: CERAD-IR was significantly associated with HOMA-IR and insulin. HbA1c was related to all the cognitive tests except AF. Among participants without obesity, HOMA-IR and insulin were both negatively associated with CERAD-IR and CERAD-DR. Odds of scoring low in DSST increased with the number of glucose metabolic risk components (odds ratio 1.94, 95% confidence interval [CI] 1.26 to 2.98). Metformin use was associated with better performance in DSST among diabetes patients (β = 4.183,95% CI 1.655 to 6.713). Conclusions: Our findings support the associations of insulin resistance and glycemic level with cognitive function in key domains, especially among adults without obesity. There is positive association between metformin use and cognition.